Effect of Microstructural Constituents on Hydrogen Embrittlement Resistance of API X60, X70, and X80 Pipeline Steels - Seung-Hyeok Shin; Dong-Kyu Oh; Sang-Gyu Kim; Byoungchul Hwang (Archives of Metallurgy and Materials)
This study describes how microstructural constituents affected the hydrogen embrittlement resistance of high-strength pipeline steels. The American Petroleum Institute (API) X60, X70, and X80 pipeline steels demonstrated complicated microstructure comprising polygonal ferrite (PF), acicular ferrite, granular bainite (GB), bainitic ferrite (BF), and secondary phases, e.g., the martensite-austenite (MA) constituent, and the volume fraction of the microstructures was dependent on alloying elements and processing conditions. To evaluate the hydrogen embrittlement resistance, a slow strain rate test (SSRT) was performed after electrochemical hydrogen charging. The SSRT results indicated that the X80 steel with the highest volume fraction of the MA constituent demonstrated relatively high yield strength but exhibited the lowest hydrogen embrittlement resistance because the MA constituent acted as a reversible hydrogen trap site.